ANALISIS DETERMINAN YANG MEMPENGARUHI KINERJA KARYAWAN (Studi Pada PT. Bank NTB Syariah Cabang Sumbawa) - Novi Kadewi Sumbawati; Wirawanzah Al-Ma'arif (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to know the effect of employees’ competence, work discipline and work environment toward employees’ performance at PT. Bank NTB Syariah Branch of Sumbawa. Type of this study was associative. Data used in this study was primary in form of communities survey toward 94 employees of PT. Bank NTB Syariah Branch of Sumbawa. The method used was partial Least Square (PLS). The results study showed that the variables of employee competence, work discipline, and work environment showed positive score. It means that all variable which consisted of three variables had significant effect toward the performance of employees of PT. Bank NTB Syariah Branch of Sumbawa. The recommendation that can be submitted by the author to PT. Bank NTB Syariah branch of Sumbawa were that the Bank NTB should pay serious attention to employees and improved employees competence, work discipline and work environment because it would improve the employees performance.